The mTOR kinase inhibitor everolimus synergistically enhances the anti‐tumor effect of the Bruton's tyrosine kinase (BTK) inhibitor PLS‐123 on Mantle cell lymphoma. Issue 1 (16th October 2017) - Li, Jiao; Wang, Xiaogan; Xie, Yan; Ying, Zhitao; Liu, Weiping; Ping, Lingyan; Zhang, Chen; Pan, Zhengying; Ding, Ning; Song, Yuqin; Zhu, Jun
Abstract : Mantle cell lymphoma (MCL) is an aggressive and incurable malignant disease. Despite of general chemotherapy, relapse and mortality are common, highlighting the need for the development of novel targeted drugs or combination of therapeutic regimens. Recently, several drugs that target the B‐cell receptor (BCR) signaling pathway, especially the Bruton's tyrosine kinase (BTK) inhibitor ibrutinib, have demonstrated notable therapeutic effects in relapsed/refractory patients, which indicate that pharmacological inhibition of BCR pathway holds promise in MCL treatment. Here, we have developed a novel irreversible BTK inhibitor, PLS‐123, that has more potent and selective anti‐tumor activity than ibrutinib in vitro and in vivo . Using in vitro screening, we discovered that the combination of PLS‐123 and the mammalian target of rapamycin (mTOR) inhibitor everolimus exert synergistic activity in attenuating proliferation and motility of MCL cell lines. Simultaneous inhibition of BTK and mTOR resulted in marked induction of apoptosis and cell cycle arrest in the G1 phase, which were accompanied by upregulation of pro‐apoptotic proteins (cleaved Caspase‐3, cleaved PARP and Bax), repression of anti‐apoptotic proteins (Mcl‐1, Bcl‐xl and XIAP), and downregulation of regulators of the G1/S phase transition (CDK2, CDK4, CDK6 and Cyclin D1). Gene expression profile analysis revealed simultaneous treatment with these agents led to inhibition of the JAK2/STAT3, AKT/mTOR signaling pathways and SGK1 expression. Finally, the anti‐tumor and pro‐apoptotic activities of combination strategy have also been demonstrated using xenograft mice models. Taken together, simultaneous suppression of BTK and mTOR may be indicated as a potential therapeutic modality for the treatment of MCL. Abstract : What's new? New treatment options are urgently needed for mantle cell lymphoma (MCL), which has a high relapse rate. In this study, the authors developed a new compound called PLS‐123, which inhibits the B‐cell receptor (BCR) signaling pathway via a kinase called BTK. In addition to being more potent and selective than previous BTK inhibitors, PLS‐123 had a synergistic effect when combined with the mTOR inhibitor everolimus, both in vitro and in vivo . Simultaneous suppression of BTK and mTOR may thus offer a more effective therapeutic strategy than targeting either pathway alone.